Radiometric characteristics of combined detectors on the basis of organic and inorganic scintillators and the use thereof in radiational situation monitoring - Tarasov, V.A.; Vydai, Yu.T.; Gorbacheva, T.E.; Ananenko, A.A. (Functional Materials, 2009)
Two types of combined detectors have been developed and manufactured. The first detector type is intended to detect the α and β radiation while the other one, for β and γ radiation. The obtained parameters of the developed detectors (background counting rate, sensitivity, and the minimum detectable activity) have provided the applicability thereof for detection of α,β and β,γ radiation in common or separately.